العلاقة الديناميكية بين الصورة الذهنية المعرفية والعاطفية للمقصد: إستكشاف تأثيراتها على نية إعادة الزيارة اتجاه الحظيرتين الوطنيتين تيكجدة والشريعة: The dynamic association betweencognitive and affective destination image: exploring their effects on revisit intention to national parks ofTikjeda and Sharia - الفكاير أمينة; زيمي سحر (Journal of North African Economies, 2025)
This study aims to investigate the dynamic among components of the destination image and the intention to revisit Sharia and Tekjda while assessing the appeal of both destinations based on distinctive traits. Data were gathered using a questionnaire distributed among actual visitors to the two destinations, and the analysis employed a Structural Equation Model with SMART PLS 4 software. The findings provided empirical support for all hypotheses. The study revealed a significant impact of the cognitive and affective destination images on revisit intention. Furthermore, differences between the two destinations were identified. This research contributes to informed decision-making in tourism by scrutinizing destination appeal and comprehending tourist behavior, thereby facilitating the formulation of more high-performing tourism strategies.